Urządzenie algorytmiczne albo utrata inteligencji - Wróbel, Szymon (Człowiek i Społeczeństwo, 2025)
As a result of the transformation of the telecommunications market and thus the creation of the automatic society (Bernard Stiegler), through the integration and subordination of analog communication, journalism and the humanities to digital industries, the process of a new algorithmic organization of the world has begun. Thomas Berns and Antoinette Rouvroy tried to think through this social situation using the concept of the algorithmic device. The novelty in this concept of the algorithmic device is the systematic, unlimited exploitation and analysis of data serving what is today called the “data economy”. A process based on massive calculations of processed data or “big data” was recommended to us by Wired editor-in-chief Chris Anderson as the „end of theory” and a new tele-objectivity (Paul Virilio). In the presented text I ask the question whether this process strengthens technodiversity and is a sign of the coming age of cosmotechnology (Yuk Hui), or whether, on the contrary, it is a sign of the twilight of human intelligence and a symptom of destruction, devastation, and the annulment of all social skills (Bernard Stiegler).